Knowledge About Maintenance of Dental And Oral Hygiene Using The Media of The Gallery Rules (Upper Grade Students of SDN Pamatan 01 Tongas Probolinggo) - Munawaroh, Rizka Zakiyatul; Sugito, Bambang Hadi; Marjianto, Agus (SURABAYA DENTAL THERAPIST JOURNAL, 2025)
Dental and oral hygiene is a major problem in the oral cavity. In general, elementary school children do not know or understand how to maintain oral hygiene. Problem statement Based on the data from the initial examination of students of SDN Pamatan 1 Tongas Probolinggo, the average OHIS is 3.64 which indicates that the dental hygiene status is in the poor category. Snakes and ladders media is a tool to provide dental health education for children. Method This type of research is descriptive with a sample size of 67 students. Measuring instruments in this study using a questionnaire to determine student knowledge about how to maintenance of dental and oral hygiene. Data analysis was carried out using percentages then averaged and presented in tables. Results The results of this study indicate that the knowledge of upper grade students of SDN Pamatan 01 Tongas Probolinggo regarding about how to maintenance of dental and oral hygiene before using snakes and ladders media in the category of less, with an average of 54% and knowledge after using snakes and ladders in the good category, with an average of 81%. Conclusion The results of this study indicate that the knowledge of upper grade students of SDN Pamatan 01 Tongas Probolinggo regarding maintenance of dental and oral hygiene before using snakes and ladders media in the category of less, and knowledge after using snakes and ladders in the good category.